Cough frequency, cough sensitivity and health status in patients with chronic cough. - Birring, S; Matos, S; Patel, R; Prudon, B; Evans, D; Pavord, I (2006)
BACKGROUND: Little is known about the frequency of cough in health and in patients with chronic cough. METHODS: We measured cough frequency and its relationship with other markers of cough severity in 20 patients with chronic cough and 9 healthy subjects using the Leicester Cough Monitor (LCM), which is an automated ambulatory digital cough monitor that records sound only. All subjects had a 6-h recording and recordings were manually counted. A subgroup of 6 normals and 6 patients with a stable chronic cough had repeat measurements up to 6 months apart. RESULTS: Mean (sem) cough counts/hour were 43(8) in patients with chronic cough and 2(1) in normals (mean difference 41; 95% confidence interval 24-59; P<0.001). The cough counts were repeatable (within subject standard deviation: 23 coughs/hour; intraclass correlation coefficient 0.8). Cough counts correlated significantly with physical (r=-0.6, P=0.03), social (r=-0.7, P=0.01) and total Leicester Cough Questionnaire (LCQ) health status scores (r=-0.6, P=0.03) and cough sensitivity (concentration of capsaicin causing 5 coughs: r=0.9, P=0.008). CONCLUSION: We have shown that there are marked differences in cough frequency between patients with chronic cough and healthy subjects, that these measurements are repeatable, and that they correlate with cough-specific health status.